2008
DOI: 10.1126/science.1141448
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Proteostasis for Disease Intervention

Abstract: The protein components of eukaryotic cells face acute and chronic challenges to their integrity. Eukaryotic protein homeostasis, or proteostasis, enables healthy cell and organismal development and aging and protects against disease. Here, we describe the proteostasis network, a set of interacting activities that maintain the health of proteome and the organism. Deficiencies in proteostasis lead to many metabolic, oncological, neurodegenerative, and cardiovascular disorders. Small-molecule or biological proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
2,031
1
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,173 publications
(2,121 citation statements)
references
References 39 publications
33
2,031
1
18
Order By: Relevance
“…The likelihood of developing diseases of protein dysfunction, such as neurodegenerative disorders, is increased upon aging, due in part to the decline of the HSR during the aging process (Ben‐Zvi, Miller, & Morimoto, 2009; Labbadia & Morimoto, 2015). Activators of the HSR have been suggested as possible therapeutic strategies for diseases of aging (Balch, Morimoto, Dillin, & Kelly, 2008; Calamini & Morimoto, 2012; Neef, Turski, & Thiele, 2010; Westerheide & Morimoto, 2005), but many of the small molecules known to modulate HSF1 activity have cytotoxicity and poor bioavailability. Our data suggest that modulating SIR‐2.1 activity may prevent an age‐associated decline in the HSR and may prevent polyglutamine aggregation in a C. elegans Huntington's disease model.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of developing diseases of protein dysfunction, such as neurodegenerative disorders, is increased upon aging, due in part to the decline of the HSR during the aging process (Ben‐Zvi, Miller, & Morimoto, 2009; Labbadia & Morimoto, 2015). Activators of the HSR have been suggested as possible therapeutic strategies for diseases of aging (Balch, Morimoto, Dillin, & Kelly, 2008; Calamini & Morimoto, 2012; Neef, Turski, & Thiele, 2010; Westerheide & Morimoto, 2005), but many of the small molecules known to modulate HSF1 activity have cytotoxicity and poor bioavailability. Our data suggest that modulating SIR‐2.1 activity may prevent an age‐associated decline in the HSR and may prevent polyglutamine aggregation in a C. elegans Huntington's disease model.…”
Section: Discussionmentioning
confidence: 99%
“…This has revealed changed expression of several genes involved in many cellular pathways, including members of HSP families. Instead of looking at physiologically induced aging effects on gene expression, we tried to determine whether individual molecular functions of small HSPs, respectively HSP70‐dependent assistance of (re)folding reactions (CG14207) or HSP70‐independent prevention of polyQ aggregation (HSP67BC), can contribute to an enhanced lifespan in line with the theory that overall protein homeostasis is important for healthy aging (Balch et al ., 2008) and that a multitude of molecular chaperones of which the expression is regulated via HSF‐1, a transcriptional regulator of stress‐inducible gene expression, are vital in both the protection against protein folding diseases and aging (Walker et al ., 2001; Morley & Morimoto, 2004; Cohen et al ., 2006). In line, previous data had already demonstrated that the HSP22, the mitochondrial D. melanogaster small HSP family member, can induce longevity (Morrow et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Proteostasis involves balanced cellular production and folding of proteins, as well as clearance of old, misfolded, and damaged proteins 5,10 . The cardiac PQC network gener ates and conserves functional pro teins, and counter acts the proteotoxic stress resulting from damaged proteins.…”
Section: The Proteostasis Network Componentsmentioning
confidence: 99%
“…After synthesis as a poly peptide chain from the genetic code, proper function of a protein relies heavily on its correct folding into a 3D native state and on various post translational modifi cations, mostly involving the addition of chem ical groups (including phosphate, acetate, and carbo hydrate). Protein maturation, transport, and ultimately breakdown is monitored and supported by various classes of proteins, collectively called 'protein quality control' (PQC) [3][4][5] . Balanced proteostasis, therefore, depends on proper PQC and is crucial for cellular and organismal health 6 .…”
mentioning
confidence: 99%